การพัฒนากระบวนการเตรียมสารสกัดสมุนไพรไทยที่มีฤทธิ์ต้านอนุมูลอิสระ - ผลประไพ ชนัญ; อุ่นทวี ศรัณยู (Thai Journal of Science and Technology, 2019)
Abstract Non-communicable diseases (NCDs) are the major causes of premature mortality in Thailand, which their abnormalities are primarily caused by free radicals. Thus, this research aimed to develop the extraction process for preparing high antioxidant extracts from Thai herbs. To screen the potent herbal plants, i.e. Sappanwood heartwood (SH), Indian gooseberry fruit (IG), Chebulic myrobalan fruit (CM), Belliric myrobalan fruit (BM) and heart-leaved moonseed stem (HM), were extracted by macerating in ethanol. The results revealed that SH extract and IG extract exhibited high potential for antioxidant activity with high total phenolic content (TPC) among other extracts. After the selected herbs were macerated in various solvents including methanol (MeOH), ethanol (EtOH) and ethyl acetate (EtOAc), the results showed that the most suitable solvent was EtOH due to the obtained extracts expressed high antioxidant activity, high TPC and high total flavonoid content (TFC). Although extraction of SH and IG by using EtOH gave the extraction yield lower than that by MeOH, this solvent is known to be low toxic and low cost. These reasons make EtOH more suitable for extracting SH and IG in community and industrial scales. Keywords: Sappanwood; Indian gooseberry; anti-oxidant activity; non-communicable disease